1983
DOI: 10.2737/so-rp-191
|View full text |Cite
|
Sign up to set email alerts
|

Aboveground weight and volume of unthinned, planted longleaf pine on West Gulf forest sites

Abstract: Volume (cubic foot) and weight predictions (green and dry) are presented in equations and tables for aboveground total tree and tree components of unthinned, planted iongleaf pine trees. The 111 sample trees, from 10 stands in Louisiana and Texas, were 10 to 44 years old and ranged from 1 to 21 inches dbh. The data for saplings (dbh < 5 inches) were analyzed separately from that of commercial sized trees (dbh >_ 5 inches). The linearized allometric model utilizes the variable D2H (squared diameter at breast he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 2 publications
4
14
1
Order By: Relevance
“…For belowground biomass we used the model reported by Samuelson et al (2014). For aboveground biomass, we fitted new models to the data reported by Baldwin and Saucier (1983). We had access to the raw dataset that consisted of 111 trees sampled in 10 unthinned stands in Louisiana and Texas, with age ranging between 10 and 44 years, and dbh ranging between 2.8 and 52.3 cm (Baldwin and Saucier, 1983).…”
Section: Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…For belowground biomass we used the model reported by Samuelson et al (2014). For aboveground biomass, we fitted new models to the data reported by Baldwin and Saucier (1983). We had access to the raw dataset that consisted of 111 trees sampled in 10 unthinned stands in Louisiana and Texas, with age ranging between 10 and 44 years, and dbh ranging between 2.8 and 52.3 cm (Baldwin and Saucier, 1983).…”
Section: Modelsmentioning
confidence: 99%
“…The goal of this study was to develop a model that can be used to analyze the effects of silviculture on C budgets in longleaf pine plantations in the southeastern U.S. To simulate in situ C pools, we developed a hybrid model that integrates a growth and yield model for longleaf pine (Gonzalez-Benecke et al, 2012) with allometric and biometric equations determined for the species (Baldwin and Saucier, 1983;Gonzalez-Benecke et al, 2014;Samuelson et al, 2014). To estimate ex situ C pool dynamics, the model used the outputs of merchantable products from the growth and yield model and current values of forest product conversion efficiencies and forest product decay rates (Gonzalez-Benecke et al, 2010a, 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Tree dbh was measured with a diameter tape. Outside-bark stemwood volume was determined with Baldwin and Saucier's (1983) formulas.…”
Section: Vegetation Sampling and Chemical Analysismentioning
confidence: 99%
“…Extrapolating to canopy level as described by Baldwin and Saucier (1983) revealed that 20.9% of applied fertilizer N was in pine foliage at the end of the growing season. There was no effect of shrub species on nitrogen concentration or NDF in pine foliage.…”
Section: Fertilizer N and Total N In Pine Foliagementioning
confidence: 99%
“…The open canopy and high light transmittance that is characteristic of longleaf pine suggests that properly selected shrubs, when grown in the alleys between tree rows, would be minimally affected by shading (Battaglia et al 2003;Hagan et al 2009). The extensive lateral root system of the tree species, however, creates the potential for interspecific competition belowground (Hagan et al 2009).…”
Section: Introductionmentioning
confidence: 98%